Mathematical modeling on various structures under coupled dynamical thermoelasticity - Singh, Bhagwan (IIT(BHU) Varanasi, 2023)
Abstract is available in the content.
Keywords: Mathematical modeling; on various structures; under coupled dynamical thermoelasticity